Effect of ACE Inhibitor Therapy on Mortality in COVID-19 Patients with Hypertension: Meta-Analysis - Dwi Trisnawati Zainal (Masters Program in Public Health, 2022)
Background: Acute respiratory syndrome Corona Virus 2 (SARS-CoV-2) can trigger the occurrence of respiratory infectious disease Coronavirus Disease 2019 (COVID-19). Patients who have comorbid health problems such as hypertension, chronic liver, cardiovascular and diabetes mellitus are more likely to experience deterioration and death. ACE inhibitor therapy in patients with hypertension has a therapeutic effect in lowering blood pressure and is able to reduce mortality rates in COVID-19 patients, but the benefits of ACE inhibitors in patients with COVID-19 are still uncertain. This study aims to determine how much influence ACE inhibitors have on COVID-19 patients with hypertension on mortality rates.Subjects and Method: This study is a systematic review and meta-analysis with the following PICO, population: COVID-19 patients with hypertension. Intervention: administration of ACE inhibitor therapy. Comparison: therapy other than ACE inhibitors. Outcome: mortality. The articles used in this study were obtained from several online databases, including Science Direct, PubMed and Google Scholar. The keywords used in the article search were: “ACE inhibitor” AND “COVID-19” AND “Hypertension” AND “mortality”. The articles included are full-text English with a cohort study design from 2020 to 2021 and report the odds ratio in multivariate analysis. The selection of articles was carried out using the PRISMA flow chart. The articles were analyzed using the Review Manager 5.4. application.Results: A total of 4 cohort studies involving 4,998 COVID-19 patients from America, China and Italy were selected for systematic review and meta-analysis. The data collected yielded information that COVID-19 patients with hypertension who were given ACE inhibitors reduced the risk of mortality 0.67 times compared to COVID-19 patients with hypertension who were not treated with ACE inhibitors (aOR= 0.67; 95% CI= 0.36 to 1.26; p= 0.210).Conclusion: ACE inhibitors can reduce the risk of mortality in COVID-19 patients with hypertension. Keywords: COVID-19, hypertension, ACE inhibitors, mortality. Correspondence:Dwi Trisnawati Zainal. Social Security Administrator for Health, Madiun, East Java. Jl. Timor 6 Madiun, East Java, Indonesia. Email: dwitrisnawatiz@gmail.com. Mobile: 081331282009.